Microscopic mechanism of calcium silicate hydrate(C-S-H) freeze-thaw cycle based on molecular dynamics - Xiaotian Lin; Yulin Wang; Henggan Li; Zihan Zhao; Huixin Zuo; Dehong Chen; Jiacan Hou (Scientific Reports)
Abstract In order to study the microstructure changes of C-S-H under the freeze-thaw cycling, the freeze-thaw cycle simulation of C-S-H is carried out based on molecular dynamics in this paper. It was found that the density of C-S-H gradually increased with time during the freezing process and gradually decreased with time during the thawing process. The larger the temperature difference, the greater the change of the density of C-S-H, and the more obvious the movement of molecules during the freeze-thaw cycle. The increase of temperature rise and fall rate will increase the density change rate and the stress of the system. As the number of freeze-thaw cycle increases, the atomic motion in C-S-H becomes more intense, and the degree of atomic motion during freeze-thaw cycle also increases with the increase of the ratio of calcium and silicon atoms (C/S) and the ratio of water molecule and silicon atoms (W/S) in C-S-H. These research results provide theoretical guidance for further exploring the freeze-thaw failure mechanism of cement-based materials.